2019
DOI: 10.1111/gcb.14803
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting resistance and resilience to extreme drought and late spring frost in five major European tree species

Abstract: Extreme climate events (ECEs) such as severe droughts, heat waves, and late spring frosts are rare but exert a paramount role in shaping tree species distributions. The frequency of such ECEs is expected to increase with climate warming, threatening the sustainability of temperate forests. Here, we analyzed 2,844 tree‐ring width series of five dominant European tree species from 104 Swiss sites ranging from 400 to 2,200 m a.s.l. for the period 1930–2016. We found that (a) the broadleaved oak and beech are sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
131
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(141 citation statements)
references
References 80 publications
(111 reference statements)
9
131
0
1
Order By: Relevance
“…Our model simulated extreme years to cause substantial decreases in forest NPP along the Swiss elevational and bioclimatic gradient, which is in line with previous studies that assessed the impact of climate extremes on forest productivity during extremely warm-dry years (Kannenberg et al, 2019;Vitali, Büntgen, & Bauhus, 2017;Vitasse et al, 2019). Additionally, our study highlights the importance of accounting for both extreme cold and/or wet years.…”
Section: Simulations Of Npp At the Country Scalesupporting
confidence: 87%
See 1 more Smart Citation
“…Our model simulated extreme years to cause substantial decreases in forest NPP along the Swiss elevational and bioclimatic gradient, which is in line with previous studies that assessed the impact of climate extremes on forest productivity during extremely warm-dry years (Kannenberg et al, 2019;Vitali, Büntgen, & Bauhus, 2017;Vitasse et al, 2019). Additionally, our study highlights the importance of accounting for both extreme cold and/or wet years.…”
Section: Simulations Of Npp At the Country Scalesupporting
confidence: 87%
“…For both species, an extremely cold growing season can have a strong negative impact on NPP that is similar in magnitude to that from extreme warm-dry years ( Figure 5). Similarly, Vitasse et al (2019) found that late frosts can impact F. sylvatica growth in a magnitude comparable to extreme drought. However, it is also important to mention that 3-PG and DGVMs in general have often overestimated the sensitivity of forest to drought, compared to observations (Klesse et al, 2018;Thomas et al, 2017).…”
Section: Simulations Of Npp At the Country Scalementioning
confidence: 82%
“…Thus, the post‐drought trajectory that a tree follows is likely dependent on numerous factors, but especially contingent on the severity, duration and timing of the drought period itself, and the post‐drought climatic conditions that could facilitate or inhibit recovery. Additional disturbances such as frost or pest‐pathogen dynamics could also compound the impacts of drought (Gazol et al 2019; Itter et al 2019; Vitasse et al 2019), though this question remains understudied in the context of legacy effects. These findings highlight the need for future studies to consider exactly what types of drought give rise to legacy effects and why.…”
Section: Introductionmentioning
confidence: 99%
“…Due to climate warming, the frequency and severity of extreme climate events such as drought, excessive temperature, and late frosts, are expected to increase [1,2]. Such extreme events are the major impact factors on agriculture worldwide affecting growth, reproduction, and yield of plants [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%